Total Factor Productivity in the Peruvian Agriculture: Estimation and Determinants - Galarza, Francisco B. (2015)
In this article, we propose an estimation of the agriculture productivity using micro data forPeru. The method used builds on recent production function’s estimation techniques developed for panel data (e.g., Gandhi et al., 2013) but using cross-section data. Data constraints urge us to impose functional forms for the estimation. In particular, we choose the constant elasticity of substitution function, which is more flexible that other functions used by prior literature in Peru (such as the Cobb-Douglas). We find no evidence of the existence of increasing returns to scale in the Peruvian agriculture, and that the productivity is positively correlated with age, sex, andeducation, and negatively correlated with the farming unit’s acreage and market power.